2002
DOI: 10.1007/s00497-002-0142-8
|View full text |Cite
|
Sign up to set email alerts
|

LP28, a lily pollen-specific LEA-like protein, is located in the callosic cell wall during male gametogenesis

Abstract: LP28, a pollen-specific LEA-like protein identified in Lilium longiflorum purportedly related to the desiccation tolerance of pollen, was localized during male gametogenesis using immuno-electron microscopy. At premeiotic interphase, LP28 label is absent from the microsporocyte. LP28 label was first detected in the cell wall of the microsporocyte at meiotic prophase I. LP28 gradually increased as the cell wall thickened. In the dyad, after the first meiotic division, LP28 label also appeared in the septum. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Late embryogenesis abundant (LEA) proteins are involved in conferring desiccation tolerance to the pollen. In lily, LP28 is a pollen-specific LEA-like protein is known which slowly accumulates in the developing pollen and generously present in the germinated pollen after hydration with their probable role in pollen maturation and pollen tube growth [103]. In this investigation, only 1 DEG was found related to LEA-like protein, for example, Ccajan_ 52697_c0_g1_i1 showing 4.57-fold down-regulation in the CMS line.…”
Section: Degs Involved In Pollen Development Potentially Related To Cmsmentioning
confidence: 63%
“…Late embryogenesis abundant (LEA) proteins are involved in conferring desiccation tolerance to the pollen. In lily, LP28 is a pollen-specific LEA-like protein is known which slowly accumulates in the developing pollen and generously present in the germinated pollen after hydration with their probable role in pollen maturation and pollen tube growth [103]. In this investigation, only 1 DEG was found related to LEA-like protein, for example, Ccajan_ 52697_c0_g1_i1 showing 4.57-fold down-regulation in the CMS line.…”
Section: Degs Involved In Pollen Development Potentially Related To Cmsmentioning
confidence: 63%
“…There is a series of signaling events in pollen-pistil interactions starting at the stigma and ending at the ovary that guide the pollen tube to reach the micropyle which do not function in vitro. Other studies have demonstrated that a pollen-speciWc protein LP28 and two transmitting tissuespeciWc proteins, 120 kDa glycoprotein and PELPIII, were also located in the callosic cell wall of developing pollen and pollen tubes growing in situ (Lind et al 1996;Mogami et al 2002;Graaf et al 2003). Therefore, it is possible that CRT found in callosic cell wall may be translocated from ER/Golgi into it and play a role in external Ca 2+ storage in pollen tubes growing in situ, while deposition of the protein in that compartment is not required in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several genes were identified that expressed either in male gametophytic or in both sporophytic and gametophytic tissues, such as a1-tubulin from Arabidopsis (Ludwig et al, 1998), LAT52 from tomato (Ursin et al, 1989) and BA42 from B. napus (Shen and Hsu, 1992). Among the male gametophyte-specific genes, some of them were expressed in early stage therefore named microspore-specific genes, such as Bp4 from Brassica napus (Albani 1990;Custers et al, 1997) and NTM19 from tobacco (Oldenhof et al, 1996;Custers et al, 1997); some of them showed expression in both stages of pollen development, such as LP28 from lily (Mogami et al, 2002) and AtSTP9 from Arabidopsis (Schneidereit et al, 2003); and most of them were expressed in late stage of pollen development therefore named pollen-specific genes. Analysis of gene expression pattern of pollens using Affymetrix GeneChips revealed that 162 genes were selectively expressed in Arabidopsis pollen (Becker et al, 2003).…”
Section: Introductionmentioning
confidence: 99%